2016
DOI: 10.1097/fbp.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neonatal treatment with two phytoestrogens on male rat sexual behavior and partner preference

Abstract: The aim of this work was to compare the effect of neonatal treatment with the phytoestrogens coumestrol (COU) and genistein (GEN), administered in equimolecular doses, on the sexual behavior and partner preference of male rats. Four groups of male rats were injected daily from day 1 to 5 with 150 µg of GEN, an equivalent amount of COU, 1 µg of β-estradiol 3-benzoato (EB), or olive oil (VEH) (control). A fifth group remained intact. In the GEN group, intromission and ejaculation latencies decreased, whereas eja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…One interesting study reported different behavioral responses as a function of BPA dose and sexual experience [46]. Males exposed to phytoestrogens were reported to have a lower frequency of mounting, intromission and ejaculation in a number of studies [42, 47-50], whereas 2 studies reported increases in these behaviors [41, 51]. In middle-aged males, chronic exposure to methoxychlor has also been shown to decrease time to ejaculation [52].…”
Section: Effects Of Edc On Sexual Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…One interesting study reported different behavioral responses as a function of BPA dose and sexual experience [46]. Males exposed to phytoestrogens were reported to have a lower frequency of mounting, intromission and ejaculation in a number of studies [42, 47-50], whereas 2 studies reported increases in these behaviors [41, 51]. In middle-aged males, chronic exposure to methoxychlor has also been shown to decrease time to ejaculation [52].…”
Section: Effects Of Edc On Sexual Behaviormentioning
confidence: 99%
“…The behavioral modifications observed differed between studies, ranging from behavior inhibition with blocked ejaculation for estradiol benzoate in males [41] to unaltered behavior for DES [42], as shown in Table 2. These discrepancies probably reflect the different doses of E2 and its analogs used.…”
Section: Effects Of Edc On Sexual Behaviormentioning
confidence: 99%
“…Los compuestos ambientales con actividad estrogénica (xenoestrógenos y fitoestrógenos) administrados durante este periodo crítico de diferenciación, tienen el potencial de afectar irreversiblemente el desarrollo del sistema endocrino-reproductivo, lo cual resulta en una disfunción reproductiva en los adultos (Masutomi et al, 2003). Se han caracterizado los efectos de estos compuestos ambientales (como algunos Fes, tales como la genisteína, coumestrol y resveratrol) en roedores, administrados durante el periodo crítico de diferenciación sexual del cerebro, resultando en una alteración en el volumen del núcleo sexual dimórfico del área preóptica (NSD-APO), en la respuesta de la hipófisis a la hormona liberadora de las gonadotropinas (GnRH), así como alteraciones en la conducta sexual (Lephart et al, 2002;Masutomi et al, 2003;Barrita, 2005;Henry y Witt, 2006;Morales-Otal et al, 2016). Estos datos aportan evidencia de que la exposición de las crías a los Fes, durante este periodo crítico, puede alterar el desarrollo neuroendocrino en la rata macho y la conducta sexual en la etapa adulta.…”
Section: Introductionunclassified